2020
DOI: 10.1021/acs.analchem.0c00208
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization-Induced Electrochemiluminescence of Insoluble Porphyrin in Aqueous Phase

Abstract: Exploring efficient and robust electrochemiluminescence (ECL) performance of liposoluble porphyrins in aqueous phase for analytical purposes especially for important biological targets is still very challenging. In this work, a novel depolymerization-induced electrochemiluminescence (DIECL) of porphyrin and β-cyclodextrin (β-CD) self-assembly through a coreactant route was discovered. Among the studied meso-tetrasubstituted porphyrins, self-assembly of 5,10,15,20-tetrakis­(4-hydroxyphenyl) porphyrin (THPP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…1] and SO 4 .− [Eq. 2] coexist in appreciable quantities [19] . An electron transfer reaction between ATPP‐TPE .− and SO 4 .− occurs in the vicinity of the electrode to generate an excited state [ATPP‐TPE*, Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1] and SO 4 .− [Eq. 2] coexist in appreciable quantities [19] . An electron transfer reaction between ATPP‐TPE .− and SO 4 .− occurs in the vicinity of the electrode to generate an excited state [ATPP‐TPE*, Eq.…”
Section: Resultsmentioning
confidence: 99%
“…For example, by facile complexation of porphyrin with amphiphilic β‐cyclodextrin (β‐CD), Wu et al. recently found an efficient depolymerization‐induced ECL strategy for applying liposoluble porphyrins in aqueous phase and recognition of fluoride [19] . On the other hand, the structural modification is considered as another promising approach for improving photophysical properties of luminophores in the aggregated state, innovated as aggregation‐induced emission (AIE) or aggregation‐induced emission enhancement (AIEE).…”
Section: Introductionmentioning
confidence: 99%
“…(2)] coexist in appreciable quantities. [19] An electron transfer reaction between ATPP-TPEC À and SO 4 C À occurs in the vicinity of the electrode to generate an excited state [ATPP-TPE*, Eq. 3],r esulting in ECL when the excited state returns to the ground state [Eq.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[18] Therefore,two judicious strategies have been explored to preserve or even improve photophysical properties of porphyrins in the aggregated state.O nt he one hand, much effort has been devoted to preventing the aggregation of porphyrins in aqueous phase by increasing their hydrophilicity.F or example,b yf acile complexation of porphyrin with amphiphilic b-cyclodextrin (b-CD), Wu et al recently found an efficient depolymerization-induced ECL strategy for applying liposoluble porphyrins in aqueous phase and recognition of fluoride. [19] On the other hand, the structural modification is considered as another promising approach for improving photophysical properties of luminophores in the aggregated state,innovated as aggregation-induced emission (AIE) or aggregation-induced emission enhancement (AIEE). Yuan and co-workers successfully changed the ACQ behavior of triphenylamine (TPA) to AIE one by smart structural modification of TPAc ore with tetraphenylethene (TPE) peripheral moiety,and the fluorescence quantum yield of this new created TPA-TPE can reach 100 %.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemiluminescence (ECL) as a powerful and promising analytical technique is a phenomenon triggered by electrochemical processes involving electron transfers near the electrode surface. ECL combines the advantages of chemiluminescence and electrochemical technologies, which provide outstanding merits of high sensitivity, simple operation, rapid response, and good stability. As we all know, an emitter is arguably a critical role in the ECL technique. The conventional chromophores often encounter a severe aggregation quenching effect, which resulted in faint ECL signals when applied to aqueous ECL, owing to the strong π–π interactions between aromatic rings.…”
Section: Introductionmentioning
confidence: 99%